A SURVEY OF SIDE EFFECTS OF IUD - H. Nafici (Tehran University of Medical Sciences, 1973)
One hundred and eight male (108) cases, which have been using Lippes Loops (I.U.D.) for contraception, were followed for five (+5) years, and unwanted pregnancies and side effects were analyzed. Our over all impression is that because of the frequency of uterine bleeding which they cause, Lippes Loops are not an ideal contraceptive method for Iranian women.